2013
DOI: 10.3354/meps10397
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between environmental characteristics of larval bluefin tuna Thunnus thynnus habitat in the Gulf of Mexico and western Mediterranean Sea

Abstract: Despite being well adapted for feeding in cold water on their North Atlantic feeding grounds, Atlantic bluefin tuna undertake long migrations to reach warm, low productivity spawning grounds in the Gulf of Mexico and Mediterranean Sea. Environmental conditions within spawning areas have been presumed to benefit larval survival, through appropriate feeding conditions, and enhanced larval retention and growth rates. However, field collections and studies to explore the potential mechanisms are rare. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…Moreover, these authors hypothesized that the complex hydrodynamic scenario resulting from the interaction of inflowing recent Atlantic surface waters and resident waters modulated by the islands' topography, characterized by the presence of mesoscale hydrographic features such as fronts and eddies, would constitute a strong retention zone and a favourable habitat for larval survival, enhancing encounter rates between tuna larvae and potential preys (Reglero et al 2012). The unsuitability of Atlantic bluefin tuna larvae of more productive coastal waters has also been reported in the Gulf of Mexico (Muhling et al 2013). These hypotheses were reinforced by the results of Koched et al (2013) in the Gulf of Gabes, which revealed the absence of Atlantic bluefin tuna larvae near the islands of Kerkennah and Djerba, placed on the wide continental shelves characterized by shallow depths and high trophic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these authors hypothesized that the complex hydrodynamic scenario resulting from the interaction of inflowing recent Atlantic surface waters and resident waters modulated by the islands' topography, characterized by the presence of mesoscale hydrographic features such as fronts and eddies, would constitute a strong retention zone and a favourable habitat for larval survival, enhancing encounter rates between tuna larvae and potential preys (Reglero et al 2012). The unsuitability of Atlantic bluefin tuna larvae of more productive coastal waters has also been reported in the Gulf of Mexico (Muhling et al 2013). These hypotheses were reinforced by the results of Koched et al (2013) in the Gulf of Gabes, which revealed the absence of Atlantic bluefin tuna larvae near the islands of Kerkennah and Djerba, placed on the wide continental shelves characterized by shallow depths and high trophic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…While some species such as SKJ spawn over large areas throughout much of the year (Nishikawa, 1978), others show much more spatiotemporally restricted spawning. BFT is the most extreme example, with the western population spawning only in the GoM and immediate surrounds from April to June (Knapp et al, 2014;Muhling et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The technique employed should include as many relevant variables as possible and combine both community and environmental data in a single step. (Muhling et al, 2010), GLM and GAM (Dingsør et al, 2007) and neural networks (Muhling et al, 2013). Unsupervised clustering techniques are also popular, mainly through the use of dendrograms (Lindley, 1986).…”
Section: Introductionmentioning
confidence: 99%